Rogue Nation : American Unilateralism and the Failure of Good Intentions - Prestowitz, Clyde, 1941- (New York Basic Books, 2003)
This work explores the unilateral impulse and shows how it helps to shape American foreign policy. Even when the need for multilateral action - and the danger of going it alone - has never been greater, the US continues to act contrary to international law, custom, and its own best interests.
Include Notes
Keywords: Unilateral acts (International law) -- United States -- Diplomatic relations -- Diplomatic relations--Philosophy -- Political consultants -- Scotland -- Politics and government